2021
DOI: 10.31557/apjcp.2021.22.6.1789
|View full text |Cite
|
Sign up to set email alerts
|

“I Just Went for the Screening, But I Did Not Go for the Results”. Utilization of Cervical Cancer Screening and Vaccination among Females at Oyibi Community

Abstract: Background: Cervical cancer screening and vaccination practices is reported to have low coverage in most developing countries. It has been reported that most women are aware of cervical cancer screening and vaccination worldwide. Nevertheless, the rate at which women participate in cervical cancer screening and vaccination was found to be low both locally and internationally. Consequently, in sub-Saharan Africa, cervical cancer screening programs have poor coverage. The aim of this study was to explore the pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Across studies, common reasons for testing for cervical cancer included determining the presence of cancer and to access early treatment. 29 , 30 , 32 For breast cancer screening, a participant's desire for early detection could be derived from knowing a person who has been diagnosed with breast cancer and undergone treatment, such as a mastectomy. 29 A further reason that steered participants to engage with screening were predisposing factors such as genital warts and other health conditions (eg, infertility).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Across studies, common reasons for testing for cervical cancer included determining the presence of cancer and to access early treatment. 29 , 30 , 32 For breast cancer screening, a participant's desire for early detection could be derived from knowing a person who has been diagnosed with breast cancer and undergone treatment, such as a mastectomy. 29 A further reason that steered participants to engage with screening were predisposing factors such as genital warts and other health conditions (eg, infertility).…”
Section: Resultsmentioning
confidence: 99%
“… 29 A further reason that steered participants to engage with screening were predisposing factors such as genital warts and other health conditions (eg, infertility). 30 , 34 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While believing that VIA screening was likely to be painful was the second most common barrier, almost two-thirds of the participants believed cervical cancer screening was unlikely to be painful. In a similar study in Nigeria, participants expressed that screening was uncomfortable rather than painful [ 51 ]. The current study demonstrated that women who believed that cervical cancer screening was likely to be painful were more likely to be classified as non-adherent than women who believed screening was unlikely to be painful.…”
Section: Discussionmentioning
confidence: 99%